Investigation of the Effects of Inlet System Configuration on the Airflow Characteristics - Shafiq, Suhaimi; R., Mamat; Nik Rosli, Abdullah (2013)
The effort towards the development of an engine that is efficient and green has become one of the biggest efforts of the major part of the automotive industry. The contribution of air quality to the engine plays an important role to increase power while minimizing the exhaust emission. The main purpose of this article is to investigate the characteristic of the air intake system of a naturally aspirated engine on a steady flow bench. The experiment was conducted using an industrial flow bench apparatus where the pressure different test pressures can be set and, at every test pressure, the valve is lifted at an increment of 1mm until the maximum possible valve lift where the flow rate is obtained in terms of cubic foot per minute or CFM. The experiment process was then repeated at different configuration. The experimental result shows that the flow rate increases with each valve lift in a linear pattern until at a certain point where the value becomes constant. The result also indicated that the flow rate increases as the different pressure increases.